2018
DOI: 10.1016/j.ultsonch.2018.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of water removing and the quality of fried purple-fleshed sweet potato in the vacuum frying by combined power ultrasound and microwave technology

Abstract: The combination of ultrasound and microwave in vacuum frying system was investigated to achieve higher drying efficiency and quality attributes of fried products. Purple-fleshed potato were used as test specimen and different power levels of microwave (0 W, 600 W, 800 W) and ultrasound (0 W, 300 W, 600 W) during vacuum frying. Drying kinetics, dielectric properties, moisture state variation and quality attributes of fried samples were measured in a vacuum frying (VF), and an innovatively designed ultrasound an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 84 publications
(43 citation statements)
references
References 63 publications
6
37
0
Order By: Relevance
“…Moreover, the ultrasound was reported to increase the heat transfer rate during frying because of micro‐vibrational effect and microstreaming effect (Kadam, Tiwari, & O'Donnell, ). Therefore, the frying process was accelerated at constant microwave power when ultrasound power was increased from 300 to 600 W. This result was in accordance with earlier work of combined ultrasound and microwave vacuum frying of purple‐fleshed chips (Su, Zhang, Bhandari, et al, ). This result can also be explained from the SEM analysis as shown in Figure .…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…Moreover, the ultrasound was reported to increase the heat transfer rate during frying because of micro‐vibrational effect and microstreaming effect (Kadam, Tiwari, & O'Donnell, ). Therefore, the frying process was accelerated at constant microwave power when ultrasound power was increased from 300 to 600 W. This result was in accordance with earlier work of combined ultrasound and microwave vacuum frying of purple‐fleshed chips (Su, Zhang, Bhandari, et al, ). This result can also be explained from the SEM analysis as shown in Figure .…”
Section: Resultssupporting
confidence: 90%
“…The oil content was found to decrease (40.29%) significantly ( p < 0.05) from 17.67% to 10.55% when ultrasound and microwave powers were increased from 300 to 600 and 1,800 to 3,000 W, respectively. Similar results were reported in a study of application of ultrasound and microwave in vacuum frying of purple‐fleshed sweet potato (Su, Zhang, Bhandari, et al, ). Quan et al () also observed similar effect of microwave on French fries with lower oil content.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Due to the rapid evaporation of surface moisture, internal moisture transferred to the fillets' surfaces with the water gradient, which was consistent with the relatively high shrinkage ratio and rehydration rate of HAD. The changes in cell structure were attributed to the moisture evaporation by the additional microwave heated (Su, Zhang, Bhandari, & Zhang, ). Figure b shows that the microscopic holes formed during the VMD process were bigger than those formed during the other processes.…”
Section: Resultsmentioning
confidence: 99%